Pengaruh good governance dan pengendalian internal terhadap kinerja aparatur pemerintah desa pada Kecamatan Wonodadi - Nada, Ayu Ni’matin; Khoiriawati, Novi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to determine the effect of implementing good governance and internal control on the performance of village government officials in 11 villages in Wonodadi District, Blitar Regency, either partially or simultaneously. The method used in this research is quantitative with the type of associative research. The sampling technique used was random sampling and used the Slovin formula, which obtained a sample of 88 respondents ang 86 data that could be processed. The data analysis in this study used validity test, reliability test, classical assumption test, and multiple regression analysis. The resultsof this study partially show that the implementation of good governance and internal control variables has a sinificant positive effect on the performance of village gpvernment officials in 11 villages in Wonodadi District, Blitar Regency. Simultaneously the application of good governance and internal control has a signficant positive effect on the performance of village government officials in 11 villages in Wonodadi District, Blitar Regency.